AKIBAT HUKUM PENJAMIN YANG MELEPASKAN HAK ISTIMEWA DALAM PERJANJIAN PENANGGUNGAN YANG DIBUAT SECARA LISAN - Angga Dewi, Ni Wayan Arika Cintya; Arsha Putra, I Putu Rasmadi (Kertha Semaya : Journal Ilmu Hukum; Vol 8 No 6 (2020), 2020)
T he aim of this study is to examine the binding strength of the suretyship agreement orally and to knowing the legal consequences of the guarantor who relinquishes the privileges in the suretyship agreement orally. This study uses normative legal research methods with a statute approach and a conceptual approach. The study result show that the obscurity of the norms of Article 1824 of the Civil Code has the potential diverged by the guarantor when the oral agreement can only be difficult for creditors in executing the assets of the guarantor and difficult to prove if resolved through litigation. Thus, the binding force of the written agreement orally is still weak because it does not have binding power to third parties so that it requires supporting evidence . The relinquishment of the guarantor's privileges results in the creditor being able to directly execute the guarantor's assets without the sale of the debtor's assets.   Keywords : Legal Consequences, Special Rights, Oral Suretyship Agreement